About contracts of continuous and instantaneous performance: time and satisfaction of the creditor’s interest - Vargas Sequeiros, Luis Diego (2024)
This article analyzes the national and international regulation of continuous and instantaneous performance contracts, focusing on the incomplete nature of this regulation and its impact on legal certainty.The authors propose a classification based on the role of time in contractual performance and satisfaction of the creditor’s interest. These criteria are presented as more precise to differentiate between continuous and instant performance contracts, facilitating their practical application.